Transforming an abandoned well into a permanent downhole receiver array: Harvey-3 case study. Issue 1 (1st December 2019) - Ricard, Ludovic; Pevzner, Roman; Sidenko, Evgenii; Tertyshnikov, Konstantin; Sharma, Sandeep; Van Gent, Dominique; Isaenkov, Roman
Summary: Fibre optic sensing is an emerging technology enabling reliable long term monitoring and surveillance of the subsurface. In this contribution, we detail the first Australian installation of a fibre optic sensing system as part of a stratigraphic well decommissioning or plug and abandon (PandA) process including preliminary results of the cementing operations. Additionally, we propose options for long term enduring research at the resulting facility.